PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PERSONAL HYGIENE SAAT MENSTRUASI DI SMP NEGERI 35 PALEMBANG - Abeer Jacinda, Aurellia Zafirah; Tamar, Miskiyah; Murbiah, Murbiah (Coping: Community of Publishing in Nursing, 2024)
Adolescents are children who experience the process of becoming adults, starting from physical, psychological changes, biological development and menarche or first menstruation which marks the beginning of the reproductive phase of their life, which is an important biological milestone. Menstruation is a natural process that occurs in every woman which is characterized by the shedding of the endometrial wall which causes bleeding from the vagina. At the time of menstruation, personal hygiene is very necessary for young women to diseases in the reproductive organs, one of them is carrying out personal hygiene during menstruation by cleaning the vagina repeatedly. One way to increase adolescent knowledge is through health education. Health education can improve people’s lifestyles, therefore people can make healthy changes. This research aims to determine the influence of personal hygiene health education during menstruation on the knowledge of young women at SMP Negeri 35 Palembang. This research used the one group pretest posttest method. The research was conducted on June 12, 2023 with 40 respondents from class VIII of SMP Negeri 35 Palembang. The knowledge value of young women before health education was 66.00 and after health education was 96.50. There was an effect of health education on young women’s knowledge about personal hygiene during menstruation at SMP Negeri 35 Palembang with a p-value of 0,000.